Persepsi Orang Tua Terhadap Pelayanan Anak Berdasarkan Gender Guru - Fajriyah, Lathifatul; Wahyudi, Rangga (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to examine parents' perceptions of the services provided by male and female teachers at PAUD Thariqul Ilmi Grogol, Kediri. Understanding parents' perceptions of teacher services is essential for improving the quality of education in early childhood institutions. This research employs a qualitative descriptive approach with data collection techniques including in-depth interviews and observation. The sample consisted of 30 parents whose children are enrolled at the institution. Data were analyzed thematically to identify parents' views and experiences regarding the interactions and teaching methods used by male and female teachers. The results indicate that parents generally hold positive perceptions of both male and female teachers. However, differences were found in terms of emotional closeness and teaching styles. Female teachers were perceived as more nurturing and emotionally connected, while male teachers were viewed as more assertive and disciplined. The study concludes that despite these perceptual differences, both male and female teachers are seen as capable of providing services that support optimal child development. These findings may serve as input for schools in enhancing teacher competencies and instructional approaches.